Physical Analysis Work for Slope Stability at Shah Alam, Selangor - Mohd Fakhrurrazi, Ishak; M. S. I., Zaini (IOP Publishing, 2018)
Slope stability analysis is performed to assess the equilibrium conditions and the safe design of a human-made or natural slope to find the endangered areas. Investigation of potential failure and determination of the slope sensitivity with regard to safety, reliability and economics were parts of this study. Ground anchor is designed to support a structure in this study. Ground anchor were implemented at the Mechanically Stabilized Earth (MSE) wall along Anak Persiaran Jubli Perak to overcome the further cracking of pavement parking, concrete deck and building of the Apartments. A result from the laboratory testing of soil sample such as index test and shear strength test were applied to the Slope/W software with regard to the ground anchors that were implemented. The ground anchors were implemented to increase the value of the factor of safety (FOS) of the MSE Wall. The value of the factor of safety (FOS) before implementing the ground anchor was 0.800 and the ground anchor was implemented the value increase to 1.555. The increase percentage of factor of safety by implementing on stability of slope was 94.38%.